A MASS COMPATIBLE UPLC METHOD FOR THE QUANTIFICATION OF IMPURITIES IN FLUTICASONE PROPIONATE NASAL SPRAY - RAO, MUGADA RAVI PRASADA; THOTA, RAMA KRISHNA; SENTHI, MAHIBALAN; MOGADATI, PAUL; ARUTLA, SRINIVAS (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The objectives of the present study were to develop and validate a mass compatible ultra-performance liquid chromatography (UPLC) method to quantify the impurities in fluticasone nasal spray, and to establish a suitable container-closure system for the formulation. Methods: A gradient method was optimized with a flow rate of 0.5 ml/min, detector wavelength-240 nm, run time-25 min and 0.1% Trifluoroacetic acid (TFA) in water as solvent A and Methanol as solvent B. Results: The developed method was linear over the range of 0.07-1.10 µg/ml for impurity-I, 0.16-2.47 µg/ml for impurity-II, 0.67-10.0 µg/ml for impurity-III, and 1.29-19.3 µg/ml for impurity-IV. The limit of quantification (LOQ) and limit of detection (LOD) were established as 0.07 and 0.02 µg/ml, 0.14 and 0.05 µg/ml, 0.59 and 0.19 µg/ml, 1.06 and 0.35 µg/ml for impurities I-IV respectively. The percent relative standard deviation (%RSD) of the replicate analysis for impurities I-IV, was within the acceptance criteria (0.4, 0.2, 0.3, and 0.1% respectively) that proved the precision of the method. The accuracy of the method was studied from 50%-150% of test concentration and the results ranged from 100.3% to 109.4%. The container-closure compatibility study revealed that the solution stored in the glass container system did not generate any additional peaks in the chromatogram. Conclusion: Hence, the developed method can be employed by quality testing laboratories to quantify impurities in fluticasone propionate nasal spray. The study also suggests that glass containers could serve as a compatible system for the storage of fluticasone propionate nasal solution.